2019
DOI: 10.1007/s10531-019-01922-5
|View full text |Cite
|
Sign up to set email alerts
|

Habitat-partitioning improves regional distribution models in multi-habitat species: a case study with the European bilberry

Abstract: Modelling the spatial distribution of multi-habitat species is challenging since they show multi-dimensional environmental responses that may vary sharply through habitats. Hence, for these species, the achievement of realistic models useful in conservation planning may depend on the appropriate consideration of habitat information in model calibration. We aimed to evaluate the role of different types of habitat predictors, along with habitat-partitioning, to improve model inference, detect non-stationary resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…At the plant-community level, the typology studied ranged from plant associations [49,50] to natural habitats [5,[51][52][53]. Interestingly, Bradter et al [49] and Fenske et al [50] indicated that increasing the vegetation hierarchical level (i.e., from habitat to plant association or species) decreases OCC accuracy, while Suárez-Seoane et al [54] demonstrated the opposite. In addition, Suárez-Seoane et al [54] and Connor et al [55] showed that vegetation classes with a narrow ecological niche had higher classification accuracy than that with a wider niche.…”
Section: From Plant Species To Land Covermentioning
confidence: 99%
See 4 more Smart Citations
“…At the plant-community level, the typology studied ranged from plant associations [49,50] to natural habitats [5,[51][52][53]. Interestingly, Bradter et al [49] and Fenske et al [50] indicated that increasing the vegetation hierarchical level (i.e., from habitat to plant association or species) decreases OCC accuracy, while Suárez-Seoane et al [54] demonstrated the opposite. In addition, Suárez-Seoane et al [54] and Connor et al [55] showed that vegetation classes with a narrow ecological niche had higher classification accuracy than that with a wider niche.…”
Section: From Plant Species To Land Covermentioning
confidence: 99%
“…Interestingly, Bradter et al [49] and Fenske et al [50] indicated that increasing the vegetation hierarchical level (i.e., from habitat to plant association or species) decreases OCC accuracy, while Suárez-Seoane et al [54] demonstrated the opposite. In addition, Suárez-Seoane et al [54] and Connor et al [55] showed that vegetation classes with a narrow ecological niche had higher classification accuracy than that with a wider niche. To improve the classification accuracy of plant communities, Tang et al [56] developed an approach that groups species into spectrally discriminating phenological groups based on a k-means classification applied to PCA axes of MODIS spectral variables.…”
Section: From Plant Species To Land Covermentioning
confidence: 99%
See 3 more Smart Citations